Analisis Persepsi Masyarakat tentang Kegiatan Palang Merah Indonesia Mengenai Donor Darah - Meisya Adelia; Siti Rodina Aisah Siregar; Usiono Usiono; Dede Kurniawan; Astary Desty Rahmadhani (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
This research leads to the results of people's perceptions about blood donation. Blood donation is an activity in the process of donating blood with the aim of blood transfusion. Meanwhile, blood transfusion is the process of transferring blood from someone who has a healthy immune system and is labeled as fulfilling the requirements for transfusion to another person. In this case, the transferred blood can be whole blood or the blood component itself. This research uses a qualitative descriptive research that uses interview techniques, goes into the field to collect data and interacts directly with (objects) of the community. Without blood donors who are intermediaries from God, you will not be able to help others. Blood donors can be in the form of whole blood and blood components. Well implemented according to the ASBP (Armed Services Blood Program) for men routine blood donors every 2 months, while for women every 3 months. Keywords: perception, blood donation, components.